Answer:
(x, y) ⟶ (x + 6, y - 4); (x, y) ⟶ (x - 6, y)
Explanation:
A translation of (x, y) ⟶ (x + 4, y – 2) means that the coordinates of the pre-image have moved four units to the right and two units down.
1. First translation
Consider point F.
It moves from (-1, 1) to F' (5,-3), so it has moved six units to the right and four units down. The translation is
(x, y) ⟶ (x + 6, y - 4)
2.Second translation
Now consider point F'. It moves from (5, -3) to F" (-1,-3), so it has moved horizontally six units to the left. The translation is
(x, y) ⟶ (x - 6, y)